STRATEGIES IN IMPROVING READING COMPREHENSION THROUGH VOCABULARY ACQUISITION - Khairil Razali; Irhami Razali (Englisia: Journal of Language, Education, and Humanities, 2013)
Vocabulary acquisition concerns on how people expand the numbers of words they understand when learning a new language. Knowing words in a second or foreign language is vitally important because the reader will be able to understand the written text well and the speaker will be able to communicate basic ideas through vocabulary even if the person does not understand how to create a grammatically correct sentence. As Madsen argued, "mastering vocabulary is the primary thing that every student should acquire in learning English" (Harold, 1983). Therefore, acquiring a sufficiently large vocabulary is one of the important tasks faced by L2 learners in order to comprehend the written texts in reading as one of the four basic features of language learning.